How new airport infrastructure promotes tourism: evidence from a synthetic control approach in German regions - Luisa Doerr; Florian Dorn; Stefanie Gaebler; Niklas Potrafke (Regional Studies, 2020)
The paper examines how new airport infrastructure influences regional tourism. Identification is based on the conversion of a military airbase into a regional commercial airport in the German state of Bavaria. The new airport opened in 2007 and promotes travelling to the touristic region of Allgäu in the Bavarian Alps. A synthetic control approach is used to show that the new commercial airport increased tourism in the Allgäu region over the period 2008–16. The positive effect is especially pronounced in the county in which the airport is located. The results suggest that new transportation infrastructure promotes regional economic development.
Keywords: L93; O18; Z38; 330; airports; tourism; regional development; transportation infrastructure; synthetic control method